2021
DOI: 10.34172/jrhs.2022.74
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Evaluation of Food Items Preferred by Adolescents under the Influence of Television Advertisements

Abstract: Background: Food and beverage advertisements on television play a significant role in food preferences, especially among children and adolescents. This study aimed to evaluate foods and beverages advertised on television and purchased by adolescents or their families using the World Health Organization (WHO) nutrient profiling model. Study design: A cross-sectional study. Methods: This cross-sectional study was performed on 2,699 students (1380 males and 1319 females) aged 11-16 in Ankara, Turkey, in 2015. Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A total of 19 published articles, were included in the review. The studies took place in Europe (Spain [ 34 ], Belgium [ 25 , 36 ], Ireland [ 30 ], the UK [ 26 , 27 ], The Netherlands [ 31 ], Turkey [ 33 ]), the USA [ 20 , 21 , 23 , 24 , 28 , 29 , 32 , 37 ], Uruguay [ 38 ], and Australia [ 22 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 19 published articles, were included in the review. The studies took place in Europe (Spain [ 34 ], Belgium [ 25 , 36 ], Ireland [ 30 ], the UK [ 26 , 27 ], The Netherlands [ 31 ], Turkey [ 33 ]), the USA [ 20 , 21 , 23 , 24 , 28 , 29 , 32 , 37 ], Uruguay [ 38 ], and Australia [ 22 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…To calculate and assess the degree of obesity/overweight of the subjects to be examined, the Body Mass Index (BMI) was mainly used. Regarding anthropometric characteristics, height and weight in four studies [ 21 , 29 , 31 , 33 ] were measured by specialized personnel according to protocols. In five studies [ 20 , 24 , 27 , 34 , 36 ], those measurements were reported by the adolescents themselves or by their guardians.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations